Subduction of continental margins and the uplift of high-pressure metamorphic rocks - Hynes, Andrew; Arkani-Hamed, Jafar; Greiling, Reinhard O. (Earth and planetary science letters, 1996)
The mechanism by which high-pressure metamorphosed continental material is emplaced at high structural levels is a major unsolved problem of collisional orogenesis. We suggest that the emplacement results from partial subduction of the continental margin which, because of its high flexural rigidity, produces a rapid change in the trajectory of the descending slab. We assume a two-fold increase in effective elastic thickness of the lithosphere as the continental margin approaches the subduction zone, and calculate the flexural profile of a thin plate for progressive downward migration of the zone of increased rigidity. We assess the effect of changes in the flexural profile on the overlying accretionary prism and mantle wedge as the continent approaches by estimating the extra stresses that are imposed on the wedge due to the bending moment exerted by the continental part of the plate. The wedges overlying the subduction zones, and the subducting slab itself, experience substantial extra compressional stress at depths of around 100 km, and extensional stress at shallower depths, as the continental margin passes through the zone of maximum curvature. The magnitudes of such extra stresses are probably adequate to effect significant deformation of the wedge and/or the descending plate, and are experienced in a time interval of less than 5 m.y. for typical subduction rates. The spatial variation of yield stresses in the region of the wedge and descending slab indicates that much of this deformation may be taken up in the crustal part of the descending slab, which is the weakest region in the deeper parts of the subduction zone. This may result in rapid upward migration of the crust of the partially subducted continental margin, against the flow of subduction. High-pressure metamorphosed terranes emplaced by the mechanism envisaged in this paper would be bounded by thrust faults below and normal faults above. Movement on the faults would have been coeval, and would have resulted in rapid unroofing of the high-pressure terranes, synchronous with arrival of the continental margin at the subduction zone and, therefore, relatively early in the history of a collisional orogen.
Elektronische Reproduktion der Druck-Ausgabe vom 25. Februar 1999
Gesehen am 06.12.2022